Structure–activity relationship of lipid core peptide-based Group A Streptococcus vaccine candidates. Issue 14 (15th July 2016) - Chan, Amy; Hussein, Waleed M.; Ghaffar, Khairunnisa Abdul; Marasini, Nirmal; Mostafa, Ahmed; Eskandari, Sharareh; Batzloff, Michael R.; Good, Michael F.; Skwarczynski, Mariusz; Toth, Istvan
Graphical abstract: Abstract: Infection with Group A Streptococcus (GAS) can result in a range of different illnesses, some of which are fatal. Currently, our efforts to develop a vaccine against GAS focuses on the lipid core peptide (LCP) system, a subunit vaccine containing a lipoamino acid (LAA) moiety which allows the stimulation of systemic antibody activity. In the present study, a peptide (J14) representing the B-cell epitope from the GAS M protein was incorporated alongside a universal T-helper epitope (P25) in four LCP constructs of different spatial orientation or LAA lengths. Through structure–activity studies, it was discovered that while the alteration of the LCP orientation had a weaker effect on immunostimulation, increasing the LAA side chain length within the construct increased antibody responses in murine models. Furthermore, the mice immunised with the lead LCP construct were also able to maintain antibody activity throughout the course of five months. These findings highlight the importance of LAA moieties in the development of intranasal peptide vaccines and confirmed that its side chain length has an effect on the immunogenicity of the structure.